From climate change to behavioral change : applying the Theory of Planned Behavior on pro-environmental behaviors - Liew, Clarissa Wan Ting (Nanyang Technological University, 2020)
Considering the relatively lagging environmental efforts put forth by the government to combat the climate crisis, individual citizens can and should step up their efforts as well to play their role. Using the Theory of Planned Behavior (TPB), a well-researched social cognitive model, we attempt to analyze individuals’ pro-environmental behavior prediction and intervention success across the globe. The study looked at pro-environmental behavior in 5 areas: (1) Waste Management, (2) Green Consumption, (3) Climate and Environment, (4) Conservation, (5) Sustainable Transport, and subsequently evaluated Singapore’s policies on climate change based on the insight we gained. We concluded that although TPB serves as a useful model for practitioners and policymakers in campaign planning for the climate crisis, there is limited optimism towards the reliable predictability of each component of behavior intention and intention onto specific actual pro-environmental behaviors. Discussion of further research on several pro-environmental behavior gaps in a bid to encourage more people to engage and maintain more of such behaviors and recommendations are discussed.